2011
DOI: 10.1364/ol.36.000166
|View full text |Cite
|
Sign up to set email alerts
|

Optical gain and laser generation in bismuth-doped silica fibers free of other dopants

Abstract: Luminescence emission and excitation spectra of bismuth-doped silica optical fibers free of other dopants have been obtained to construct an emission-excitation map in a wide wavelength range of 400-1600 nm. The main low-lying energy levels of the bismuth active centers in such fibers have been determined. For the first time (to our knowledge), optical gain and lasing have been obtained in such fibers. A gain of 8 dB has been achieved with a pump power of 340 mW, and a cw fiber laser emitting at 1460 nm with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 9 publications
3
33
0
1
Order By: Relevance
“…The emission lifetime at room temperature typically ranges from hundreds of microseconds to several milliseconds. An additional absorption band at 1400 nm was observed by Dvoyrin et al and Bufetov et al in bismuth doped silica glass [1,[3][4][5]. In a non-oxide glass, Hughes et al reported absorption at ~1180nm, fluorescence lifetime of 175 µs at room temperature for an emission peak at ~1500nm [6].…”
Section: Consequences For Nir-emitting Bi-doped Glassesmentioning
confidence: 82%
See 4 more Smart Citations
“…The emission lifetime at room temperature typically ranges from hundreds of microseconds to several milliseconds. An additional absorption band at 1400 nm was observed by Dvoyrin et al and Bufetov et al in bismuth doped silica glass [1,[3][4][5]. In a non-oxide glass, Hughes et al reported absorption at ~1180nm, fluorescence lifetime of 175 µs at room temperature for an emission peak at ~1500nm [6].…”
Section: Consequences For Nir-emitting Bi-doped Glassesmentioning
confidence: 82%
“…For comparison, Bi-doped oxide glasses were prepared from analytical grade Al(OH) 3 X-ray diffraction patterns of the samples were recorded with a Rigaku D/max-IIIA X-ray diffractometer (40kV, 1.2°min −1 , 40 mA, Cu-Kα1, λ = 1.5405Å). Raman spectra were measured on a Horiba Jobin Yvon LabRAM Aramis spectrometer equipped with a 633 nm He-Ne laser.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations